Implementation of an Electronic Performance Management System and Its Contribution to Employee Performance in Public Sector Organizations - Mahlida Listiani; Musmuliadi Musmuliadi; Aini Aini (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the implementation of an electronic performance management system and its contribution to employee performance in a public sector organization. The increasing adoption of digital governance requires government institutions to enhance accountability, transparency, and efficiency through technology-based performance management systems. Using a qualitative research approach, data were collected through in-depth interviews with employees, supervisors, and administrative officials, complemented by field observations and document analysis. The study explores how the electronic performance system is implemented and how it influences employee performance in daily administrative activities. The findings indicate that the system contributes positively to employee discipline, task accountability, work monitoring, and performance evaluation processes. Employees perceive the system as an effective tool for documenting work achievements, improving transparency, and facilitating communication between supervisors and staff. However, several challenges remain, including technical constraints, varying levels of digital competency, and the need for stronger organizational support to maximize system utilization. The effectiveness of the electronic performance system is influenced by leadership commitment, user readiness, system reliability, and the integration of performance evaluation mechanisms. The study highlights the importance of continuous capacity building, system refinement, and institutional support to optimize digital performance management practices and strengthen employee performance within public sector organizations.